Patient safety in prescription and medication administration: an integrative review (Research, Society and Development, 2020)
The present study has as its theme the patient's safety, which is the action aimed at avoiding adverse events in the health care provided, with emphasis on actions aimed at continuous improvement. Currently, in the hospital environment, there has been an increase in the incidence of adverse patient outcomes, highlighting errors in prescription and medication administration. This work aims to analyze patient safety in a hospital environment by the nursing team through a literary search. The same was developed through a bibliographical review of the integrative type of literature that approaches a current knowledge about a specific theme. After the research, it can be verified that there are a number of factors that can interfere in the hospital care process, such as illegibility in prescriptions, failures in preparing and dilution of medicines, and failure of communication between professionals, among which, in great majority, result in negative aspects for the quality of life of hospitalized patients. Therefore, it was noticed the need to subsidize new studies on the subject, as it was noticed a shortage of publications and knowledge regarding patient safety, which is a culture that should be established in the practice of care, since it aims at reducing unnecessary damage to health care.